High-performance human resource practices, organizational identification and employee commitment: the moderating role of organizational culture - Yang, Yifan; Mostafa, Ahmed Mohammed Sayed (Frontiers in Psychology, 2024)
Purpose: Drawing on social exchange and social identity theories, this study examines the mediating role of organizational identification on the relationship between high-performance human resource practices (HPHRPs) and employee commitment. The study further examines the moderating role of organizational culture in this mediated relationship.A cross-sectional survey was conducted with 340 employees from state-owned enterprises in China, and SPSS was used to test the hypothesized relationships.The results indicate that organizational identification acts as a mediator of the relationship between HPHRPs and employee commitment. Additionally, organizational culture moderates the strength of this mediated relationship, affecting the degree to which HPHRPs foster commitment.Originality: This study contributes to the literature by integrating social exchange and social identity theories to explain the psychological mechanisms underlying the employee-organization relationship.It also extends the understanding of how organizational identification mediates the link between HPHRPs and commitment, and how organizational culture moderates these effects, providing a more comprehensive understanding of these interrelated dynamics in organizational settings.